The Educational Values as Reelected in Harper Lee Novel’s to Kill A Mocking Bird - Jayaputri, Herlandri Eka (LPPM Universitas Advent Indonesia, 2022)
This study aims to describe the good characterizations of the main characters, the plot, and the educational values in the novel To Kill a Mockingbird by Harper Lee. This current study employed the qualitative method. The research provided the secondary data derived from To Kill a Mockingbird Novel by Harper Lee. For the data collection, document analysis was used as the researcher read the novel, collected suitable data, made sense of the data, and selected the unit of analysis (Satu Elo et al., 2014). The results of this research are as follows; the first, the good characterization of the novel is curious, diligent, wise, caring, creative, and brave. The second, plot of the novel is the regressive plot because the novel talked about the experience of Scout and Jem and it is described using the theory of Tennyson in Subhan as follows; exposition, rising action, crisis, falling action, and resolution. Third, the educational values of the novel are divided into four elements namely; values of religious education, values of moral education, values of social education, and values of cultural education.